A miticidal composition, its preparation and use

CN121359718BActive Publication Date: 2026-10-16HUANGGANG NORMAL UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511936549.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-10-16
Estimated Expiration
2045-12-22

AI Technical Summary

Technical Problem

但上述方案并未解决现有药剂润湿与铺展、附着力低、稳定性差的问题

Benefits of technology

1.从组分设计上看,本方案的杀螨组合物通过壳聚糖改性填料、成膜聚合物在叶面形成牢固结合的载药膜层,直接解决了常规药液附着力弱、易被雨水冲刷的难题;采用三硅氧烷聚氧乙烯醚显著改善药液在疏水叶面的铺展性能,克服了覆盖不均和药液滚落问题;乙螨唑与烷基乙基磺酸盐的特定比例复配实现了对不同螨态的同时防治;同时,二氧化硅包覆的纳米二氧化钛在保障制剂储存稳定性的前提下,最终实现药膜的环境友好降解。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of biological pesticides, in particular to a kind of miticides composition, preparation method and application thereof, comprising the following components: active ingredient 30-60 parts;Film-forming polymer 8-15 parts;Chitosan modified filler 20-60 parts;Photosensitizer 1-3 parts;Pore-forming agent 3-7 parts;Dispersing agent 4-8 parts;Wetting agent 2-4 parts;Wherein, the active ingredient is etoxazole and alkyl ethyl sulfonate composition;Wherein, the photosensitizer is silica-coated nanometer titanium dioxide.The present application solves the three major problems of poor spreading, easy flushing and instability of traditional liquid miticides by component coordination combination, and realizes the unity of long-acting protection and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biological pesticides, specifically to an acaricidal composition, its preparation method, and its application. Background Technology

[0002] Currently used acaricides in the field, especially liquid formulations (such as emulsifiable concentrates and water-in-oil emulsions) commonly used for rapid action, suffer from three prominent technical shortcomings: 1. The pesticide solution is difficult to effectively wet and spread on hydrophobic plant leaves, resulting in uneven coverage, large amounts of solution rolling off, and extremely low utilization rate; 2. Even if successful deposition occurs, the protective layer formed by conventional pesticide solutions has weak adhesion to the leaf surface and is easily washed away by rain, resulting in a short-lasting effect and forcing farmers to apply the pesticide repeatedly; 3. Many liquid formulations containing complex adjuvant systems have poor physical and chemical stability, and are prone to stratification, precipitation, or decomposition of active ingredients during storage, affecting efficacy and shortening shelf life. These problems collectively lead to pesticide waste, increased costs, and environmental pollution. Therefore, there is an urgent need in this field for a new formulation and formulation of acaricides that can simultaneously achieve excellent foliar spread, strong rain resistance, and intrinsic stability.

[0003] In the prior art, CN 104996438 A discloses an acaricidal composition, the raw materials of which are ivermectin and etoxazole. This invention, through extensive indoor research, has screened a compound composition of ivermectin and etoxazole. Ivermectin and etoxazole have different mechanisms of action, and their combination has a good synergistic effect within a certain range, reducing pesticide usage, lowering pesticide residues on crops, and reducing environmental pollution; it is safe for humans and animals, has good environmental compatibility, and prevents mites from developing resistance. CN 118661737 B discloses an acaricidal composition; the active ingredients of the acaricidal composition include active ingredient A and active ingredient B; active ingredient A is a compound of formula (I), and active ingredient B is selected from any one of flupentiofenox, Acynonapyr, or bisulflufen; the mass ratio of active ingredient A to active ingredient B is 1:30 to 56:1. The acaricidal composition or formulation of the present invention can enhance efficacy, broaden the acaricidal spectrum, reduce usage costs, reduce dosage, prolong the duration of effect, and delay the development of drug resistance. However, the above solutions do not solve the problems of low wetting and spreading properties, low adhesion, and poor stability of existing agents. Summary of the Invention

[0004] To address the aforementioned problems, this invention proposes an acaricide composition, its preparation method, and its application. Through the coordinated combination of components, a robust and biodegradable foliar film is constructed, solving the three major problems of poor spreading, easy rinsing, and instability of traditional liquid acaricides, thus achieving a balance between long-lasting protection and environmental friendliness.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: An acaricide composition comprising, by weight, the following components: 30-60 parts of active ingredient; 8-15 parts of film-forming polymer; 20-60 parts of chitosan-modified filler; 1-3 parts photosensitizer; 3-7 parts of pore-forming agent; 4-8 parts dispersant; 2-4 parts wetting agent; The active ingredient is a combination of etoxazole and alkyl ethyl sulfonate; The photosensitizer is silicon dioxide-coated nano-titanium dioxide.

[0006] The technical solution of this invention achieves a long-lasting acaricidal effect and reduces the number of applications through the synergistic effect of its components. This solution overcomes the application bottleneck caused by the hydrophobicity of etoxazole in traditional formulations: in conventional spraying, the hydrophobic surface of etoxazole makes it difficult for the solution to spread on waxy leaves, and the crystals formed after water evaporation have weak adhesion to the leaf surface, easily detaching due to dew, rain, or slight physical friction, resulting in short-lived efficacy and low utilization. This invention introduces chitosan-modified filler as the core carrier. During the spray drying process, the chitosan on the filler surface and the film-forming polymer in the reagent synergistically form a network of biopolymer membranes with both hydrophilic groups and hydrophobic segments. This membrane is tightly anchored to the waxy layer of the leaf surface through strong hydrogen bonds and electrostatic interactions, thereby firmly encapsulating and fixing the hydrophobic etoxazole particles to the leaf surface, forming a durable protective layer resistant to rain erosion. Meanwhile, the polyethylene glycol pore-forming agent creates pores within the membrane through its water solubility, ensuring gas permeability of the drug membrane under high adhesion strength; while the silica-coated nano-titanium dioxide, while ensuring storage stability, ultimately achieves environmentally friendly degradation of the drug membrane.

[0007] Preferably, the mass ratio of etoxazole to alkyl ethyl sulfonate is 1:0.5-1:2; the wetting agent is trisiloxane polyoxyethylene ether; the pore-forming agent is polyethylene glycol; the dispersant is polycarboxylate or lignin sulfonate; and the film-forming polymer is one or more of chitosan or polyvinyl alcohol.

[0008] Preferably, the mass ratio of etoxazole to alkyl ethyl sulfonate is 1:0.5-1:2. This ratio balances the control effects of both on mite eggs, larvae, and adult mites, avoiding excessive use of any single component. The wetting agent is trisiloxane polyoxyethylene ether, which improves the coverage of the pesticide solution on hydrophobic leaf surfaces due to its super-spreading properties. The pore-forming agent is polyethylene glycol, whose water solubility ensures the formation of stable, breathable micropores in the pesticide film. The dispersant is a compound of polycarboxylate and lignin sulfonate, which, through the synergistic effect of steric hindrance and electrostatic repulsion, ensures rapid disintegration and suspension of the powder in water.

[0009] Preferably, the chitosan-modified filler is prepared by: S1a. Dissolve 5-20 parts by weight of chitosan in 200-500 parts by weight of acetic acid solution with a mass concentration of 1-3% to prepare chitosan acid solution; S1b. Disperse 100 parts by weight of the filler matrix in the chitosan acid solution obtained in step S1a, and stir at 300-500 rpm for 1-2 hours at 40-60℃. S1c. Under stirring conditions, slowly add an alkaline precipitant to the system obtained in step S1b to adjust the pH of the system to 9.0-10.0, and then age it for 0.5-1 hour under the same conditions; S1d. The material after aging in step S1c is filtered, the filter cake is washed with deionized water until the filtrate is neutral, then dried at 60-80℃ until the moisture content of the material is less than 3.0%, and finally pulverized to obtain the chitosan modified filler.

[0010] The chitosan dosage (5-20 parts) and acetic acid concentration (1-3%) ensure complete dissolution of chitosan and the formation of an effective coating layer. Excessive dosage will lead to an overly viscous solution, affecting dispersion uniformity, while insufficient dosage will result in incomplete coating. An adsorption temperature of 40-60℃ can accelerate molecular motion and promote adsorption while avoiding excessive temperature that could lead to chitosan degradation. Adjusting the pH to 9.0-10.0 is a crucial step, as chitosan has the lowest solubility under these conditions and can be uniformly deposited on the filler surface in a gel state to form a stable bond. A stirring speed of 300-500 rpm ensures that the filler is fully suspended and in uniform contact with the chitosan. Too low a speed will lead to sedimentation and agglomeration, while too high a speed will cause shear damage. A drying temperature of 60-80℃ can quickly remove moisture while avoiding high temperature that could cause chitosan denaturation and loss of film-forming properties. Controlling the final moisture content to below 3.0% ensures product storage stability and subsequent processing fluidity. This method, through precise control of parameters at each stage, achieves uniform and firm coating of chitosan on the filler surface, laying the material foundation for the subsequent formation of a stable and breathable foliar film. Preferably, the filler matrix is ​​selected from at least one of kaolin, diatomaceous earth, attapulgite, light calcium carbonate, fumed silica, or bentonite.

[0011] Preferably, the alkaline precipitant in step S1c is an aqueous solution of sodium hydroxide or sodium carbonate.

[0012] Preferably, the method for preparing the silica-coated nano-titanium dioxide is as follows: S2a. Disperse 1 part by weight of nano-titanium dioxide powder in a mixed solvent consisting of 50-100 parts by weight of ethanol and 10-20 parts by weight of deionized water, and sonicate for 10-20 minutes to form a uniform suspension. S2b. Under room temperature and stirring conditions, add 1-5 parts by mass of ammonia water with a mass concentration of 25-28% as a catalyst to the suspension obtained in step S2a; S2c. Under stirring conditions, add 0.1-0.5 parts by mass of tetraethyl orthosilicate dropwise to the system of step S2b, control the dropping rate to complete the dropping in 1-2 hours, and continue the reaction for 2-4 hours after the dropping is completed; S2d. After the reaction is complete, the product is centrifuged, the precipitate is washed with ethanol 2-3 times, and then dried at 60-80℃ to obtain the silica-coated nano-titanium dioxide.

[0013] In the above preparation process, the mixed solvent of ethanol and water (50-100:10-20) provides a suitable polar environment for the hydrolysis reaction, ensuring the appropriate hydrolysis of tetraethyl orthosilicate; 1-5 parts by weight of 25-28% ammonia water acts as a catalyst to provide an alkaline environment, but excessive amounts will cause precipitation to be too rapid and affect the uniformity of coating; 0.1-0.5 parts by weight of tetraethyl orthosilicate corresponds to a mass ratio of titanium dioxide to silicon dioxide of 1:0.1-0.5 in the final product; slow dropwise addition over 1-2 hours ensures uniform hydrolysis and condensation of the silicon dioxide precursor, avoiding localized rapid precipitation; subsequent reaction over 2-4 hours ensures the coating layer is fully cured and stable; a drying temperature of 60-80℃ effectively removes the solvent while avoiding cracking of the coating layer due to high temperature. This solution also discloses a method for preparing the above-mentioned acaricide composition, the method comprising the following steps: S1. Preparation of chitosan-modified fillers; S2. Preparation of silica-coated nano-titanium dioxide; S3. Mixing and Grinding: Weigh the chitosan-modified filler obtained in step S1, the active ingredient, the photosensitizer obtained in step S2, the porogen, the dispersant, and the wetting agent according to the specified proportions. Add the weighed components into the mixer for the first mixing, which takes 10-15 minutes. The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be no greater than 15μm. The pulverized material is then mixed a second time for 20-30 minutes to obtain a wettable powder.

[0014] This solution also discloses a method for applying the above-mentioned acaricidal composition to control plant mites, wherein the acaricidal composition is dispersed in 300-800 times its volume of water to form a suspension, and then sprayed onto the plant surface.

[0015] Preferably, before spraying, an acidity regulator, such as acetic acid or citric acid, is added to the suspension to adjust its pH value to 5.0-6.0; the application rate during spraying is 30-60L per acre.

[0016] Adjusting the pH to a slightly acidic range of 5.0-6.0 primarily considers three factors: Chitosan's solubility characteristics: Chitosan dissolves by protonation of amino groups at pH < 6.5. This pH range ensures its complete dissolution from the filler surface and its film-forming effect; Crop safety: Strong acidity (pH < 4.0) may cause leaf burn, while a slightly acidic environment is safe for most crops; Pesticide stability: Too low a pH may affect the chemical stability of some pesticide components. The application rate is set at 30-60 L / acre based on: Coverage efficiency: Below 30 L / acre, it is difficult to guarantee full leaf coverage; above 60 L / acre, it will lead to pesticide runoff; Film-forming requirements: A moderate application rate ensures that chitosan forms a continuous and uniform film layer on the leaf surface; Economic benefits: Excessive application rate increases water consumption and operation time.

[0017] Preferably, the plant pest is at least one of the following: spider mite, citrus red spider mite, scabra mite, gall mite, tarsiforme mite, or tufted spider mite; and the plant is at least one of the following: citrus, vegetable, fruit tree, or tea tree.

[0018] Compared to existing technologies, the technical advantages of this solution are: 1. From the perspective of component design, the acaricide composition of this solution forms a firmly bonded drug-loaded film layer on the leaf surface through chitosan-modified filler and film-forming polymer, directly solving the problems of weak adhesion and easy wash-off by conventional pesticide solutions; the use of trisiloxane polyoxyethylene ether significantly improves the spreading performance of the pesticide solution on hydrophobic leaf surfaces, overcoming the problems of uneven coverage and pesticide roll-off; the specific ratio of etoxazole and alkyl ethyl sulfonate achieves simultaneous control of different mite life stages; at the same time, the silica-coated nano-titanium dioxide ensures the storage stability of the formulation and ultimately achieves environmentally friendly degradation of the pesticide film.

[0019] From a process control perspective, the effectiveness of functional components was ensured by precisely controlling the coating parameters of chitosan-modified fillers and the coating thickness of photosensitizers; controlling the particle size of all solid components to D90≤15μm ensured film uniformity and formulation suspension; adjusting the pH to 5.0-6.0 and controlling the application rate to 30-60L / acre during the application stage optimized film formation conditions and leaf coverage, thus systematically solving the defects of traditional liquid formulations in terms of leaf spreading, rain washout, and storage stability.

[0020] Furthermore, in this formulation, chitosan, while fulfilling its core film-forming and leaf-attachment functions, imparts broad-spectrum antibacterial activity to the composition. This characteristic enables the acaricide composition to form a long-lasting protective film against mites while also preventing some plant diseases caused by fungi or bacteria, achieving a synergistic effect of "dual prevention of diseases and pests," thus enhancing the product's comprehensive pest control value and economic efficiency. Detailed Implementation

[0021] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] General Implementation Examples An acaricide composition comprising, by weight, the following components: 30-60 parts of active ingredient; 8-15 parts of film-forming polymer; 20-60 parts of chitosan-modified filler; 1-3 parts photosensitizer; 3-7 parts of pore-forming agent; 4-8 parts dispersant; 2-4 parts wetting agent; The active ingredient is a combination of etoxazole and alkyl ethyl sulfonate; The photosensitizer is silicon dioxide-coated nano-titanium dioxide.

[0023] In some preferred embodiments, the mass ratio of etoxazole to alkyl ethyl sulfonate is 1:0.5-1:2; the wetting agent is trisiloxane polyoxyethylene ether; the pore-forming agent is polyethylene glycol, preferably PEG6000; the dispersant is polycarboxylate or lignin sulfonate, preferably potassium polycarboxylate or potassium lignin sulfonate; and the film-forming polymer is one or more of chitosan or polyvinyl alcohol PVA-1092.

[0024] In some preferred embodiments, the chitosan-modified filler is prepared by: S1a. Dissolve 5-20 parts by weight of chitosan in 200-500 parts by weight of acetic acid solution with a mass concentration of 1-3% to prepare chitosan acid solution; S1b. Disperse 100 parts by weight of the filler matrix in the chitosan acid solution obtained in step S1a, and stir at 300-500 rpm for 1-2 hours at 40-60℃. S1c. Under stirring conditions, slowly add an alkaline precipitant to the system obtained in step S1b to adjust the pH of the system to 9.0-10.0, and then age it for 0.5-1 hour under the same conditions; S1d. The material after aging in step S1c is filtered, the filter cake is washed with deionized water until the filtrate is neutral, then dried at 60-80℃ until the moisture content of the material is less than 3.0%, and finally pulverized to obtain the chitosan modified filler.

[0025] In some preferred embodiments, the filler matrix is ​​selected from at least one of kaolin, diatomaceous earth, attapulgite, light calcium carbonate, fumed silica or bentonite, and satisfies D90≤15μm.

[0026] In some preferred embodiments, the alkaline precipitant in step S1c is an aqueous solution of sodium hydroxide or sodium carbonate.

[0027] In some preferred embodiments, the method for preparing the silica-coated nano-titanium dioxide is as follows: S2a. Disperse 1 part by weight of nano-titanium dioxide powder in a mixed solvent consisting of 50-100 parts by weight of ethanol and 10-20 parts by weight of deionized water, and sonicate for 10-20 minutes to form a uniform suspension. S2b. Under room temperature and stirring conditions, add 1-5 parts by mass of ammonia water with a mass concentration of 25-28% as a catalyst to the suspension obtained in step S2a; S2c. Under stirring conditions, add 0.1-0.5 parts by mass of tetraethyl orthosilicate dropwise to the system of step S2b, control the dropping rate to complete the dropping in 1-2 hours, and continue the reaction for 2-4 hours after the dropping is completed; S2d. After the reaction is complete, the product is centrifuged, the precipitate is washed with ethanol 2-3 times, and then dried at 60-80℃ to obtain the silica-coated nano-titanium dioxide.

[0028] A method for preparing any of the above-mentioned acaricidal compositions, the method comprising the following steps: S1. Preparation of chitosan-modified fillers; S2. Preparation of silica-coated nano-titanium dioxide; S3. Mixing and Grinding: Weigh the chitosan-modified filler obtained in step S1, the active ingredient, the photosensitizer obtained in step S2, the porogen, the dispersant, and the wetting agent according to the specified proportions. Add the weighed components into the mixer for the first mixing, which takes 10-15 minutes. The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be no greater than 15μm. The pulverized material is then mixed a second time for 20-30 minutes to obtain a wettable powder.

[0029] Example 1 An acaricide composition comprising, by weight, the following components: 40 parts of etoxazole and 20 parts of sodium alkyl ethyl sulfonate; 11.5 parts chitosan; 40 parts of chitosan-modified filler; Two parts of silica-coated nano-titanium dioxide; PEG 6000, 5 parts; Potassium polycarboxylate 6 parts; 3 parts of trisiloxane polyoxyethylene ether; The preparation method of chitosan-modified filler is as follows: 12.5 parts by weight of chitosan were dissolved in 350 parts by weight of acetic acid solution with a mass concentration of 2% to prepare chitosan acid solution; 100 parts by weight of kaolin were dispersed in the resulting chitosan acid solution and stirred at 400 rpm for 1.5 hours at 50°C. Under stirring conditions, a 3% sodium hydroxide solution was slowly added to the resulting system to adjust the pH value of the system to 9.5, and then aged for 0.75 hours under the same conditions. The aged material is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. Then it is dried at 70°C until the moisture content of the material is 2.5%. Finally, it is pulverized to obtain the chitosan modified filler.

[0030] The preparation method of silica-coated nano-titanium dioxide is as follows: One part by mass of nano-titanium dioxide powder was dispersed in a mixed solvent consisting of 75 parts by mass of ethanol and 15 parts by mass of deionized water, and ultrasonically treated for 15 minutes to form a uniform suspension. Under room temperature and stirring conditions, 3 parts by mass of ammonia water with a mass concentration of 26.5% were added to the resulting suspension as a catalyst; Under stirring conditions, 0.3 parts by mass of tetraethyl orthosilicate were added dropwise to the system, with the dropping rate controlled to be completed in 1.5 hours, and the reaction continued for 3 hours after the addition was completed. After the reaction was completed, the product was centrifuged, the precipitate was washed three times with ethanol, and then dried at 70°C to obtain the silica-coated nano-titanium dioxide.

[0031] A method for preparing the above-mentioned acaricide composition includes the following steps: Weigh the obtained chitosan-modified filler, active ingredient, photosensitizer, pore-forming agent, dispersant, and wetting agent according to the specified ratio; Add the weighed components into the mixer for the first mixing, and mix for 12 minutes. The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be 12μm. The pulverized material is then mixed a second time for 25 minutes to obtain a wettable powder.

[0032] Example 2 An acaricide composition comprising, by weight, the following components: 20 parts etoxazole and 10 parts sodium alkyl ethyl sulfonate; 8 parts of polyvinyl alcohol (PVA-1092); 60 parts of chitosan-modified filler; One part of silica-coated nano-titanium dioxide; PEG 6000, 7 parts; 4 parts potassium lignosulfonate; 4 parts of trisiloxane polyoxyethylene ether; The preparation method of chitosan-modified filler is as follows: Five parts by weight of chitosan were dissolved in 500 parts by weight of acetic acid solution with a mass concentration of 1% to prepare chitosan acid solution. 100 parts by weight of diatomaceous earth were dispersed in the obtained chitosan acid solution and stirred at 500 rpm for 1 hour at 40°C. Under stirring conditions, a 5% sodium carbonate solution was slowly added to the resulting system to adjust the pH value of the system to 9.0, and then aged for 1 hour under the same conditions. The aged material is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. Then it is dried at 80°C until the moisture content of the material is 1.5%. Finally, it is pulverized to obtain the chitosan modified filler.

[0033] The preparation method of silica-coated nano-titanium dioxide is as follows: One part by mass of nano-titanium dioxide powder was dispersed in a mixed solvent consisting of 50 parts by mass of ethanol and 20 parts by mass of deionized water, and ultrasonically treated for 20 minutes to form a uniform suspension. Under room temperature and stirring conditions, 1 part by mass of ammonia water with a mass concentration of 28% was added to the resulting suspension as a catalyst. Under stirring conditions, 0.1 parts by mass of tetraethyl orthosilicate were added dropwise to the system, and the dropping rate was controlled to be completed in 2 hours. After the addition was completed, the reaction continued for 4 hours. After the reaction was completed, the product was centrifuged, the precipitate was washed twice with ethanol, and then dried at 60°C to obtain the silica-coated nano-titanium dioxide.

[0034] A method for preparing the above-mentioned acaricide composition includes the following steps: Weigh the obtained chitosan-modified filler, active ingredient, photosensitizer, pore-forming agent, dispersant, and wetting agent according to the specified ratio; Add the weighed components into the mixer for the first mixing, and mix for 15 minutes. The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be 10μm. The pulverized material is then mixed a second time for 30 minutes to obtain a wettable powder.

[0035] Example 3 An acaricide composition comprising, by weight, the following components: 20 parts etoxazole and 40 parts sodium alkyl ethyl sulfonate; 15 parts chitosan; 20 parts of chitosan-modified filler; Three parts of silica-coated nano-titanium dioxide; PEG 6000, 3 parts; 8 parts of potassium polycarboxylate; 2 parts of trisiloxane polyoxyethylene ether; The preparation method of chitosan-modified filler is as follows: 20 parts by weight of chitosan were dissolved in 200 parts by weight of acetic acid solution with a mass concentration of 3% to prepare chitosan acid solution; 100 parts by weight of attapulgite were dispersed in the obtained chitosan acid solution and stirred at 300 rpm for 2 hours at 60°C. Under stirring conditions, a 1% sodium hydroxide solution was slowly added to the resulting system to adjust the pH value of the system to 10.0, and then aged for 0.5 hours under the same conditions. The aged material is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. Then it is dried at 60°C until the moisture content of the material is 2.8%. Finally, it is pulverized to obtain the chitosan modified filler.

[0036] The preparation method of silica-coated nano-titanium dioxide is as follows: One part by mass of nano-titanium dioxide powder was dispersed in a mixed solvent consisting of 100 parts by mass of ethanol and 10 parts by mass of deionized water, and ultrasonically treated for 10 minutes to form a uniform suspension. Under room temperature and stirring conditions, 5 parts by mass of ammonia water with a mass concentration of 25% were added to the resulting suspension as a catalyst. Under stirring conditions, 0.5 parts by mass of tetraethyl orthosilicate were added dropwise to the system, with the dropping rate controlled to be completed in 1 hour, and the reaction continued for 2 hours after the addition was completed. After the reaction was completed, the product was centrifuged, the precipitate was washed three times with ethanol, and then dried at 80°C to obtain the silica-coated nano-titanium dioxide.

[0037] A method for preparing the above-mentioned acaricide composition includes the following steps: Weigh the obtained chitosan-modified filler, active ingredient, photosensitizer, pore-forming agent, dispersant, and wetting agent according to the specified ratio; Add the weighed components into the mixer for the first mixing, and mix for 10 minutes. The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be 15μm. The pulverized material is then mixed a second time for 20 minutes to obtain a wettable powder.

[0038] Example 4 An acaricide composition comprising, by weight, the following components: 24 parts of etoxazole and 36 parts of sodium alkyl ethyl sulfonate; Chitosan and polyvinyl alcohol PVA-1092 were mixed in a 1:1 mass ratio to form 12 parts; 50 parts of chitosan-modified filler; 2.5 parts of silica-coated nano-titanium dioxide; PEG 6000, 4 parts; Five parts of potassium polycarboxylate and potassium lignosulfonate were mixed in a mass ratio of 1:1. 3.5 parts of trisiloxane polyoxyethylene ether; The preparation method of chitosan-modified filler is as follows: Dissolve 15 parts by weight of chitosan in 400 parts by weight of acetic acid solution with a mass concentration of 2.5% to prepare chitosan acid solution; 100 parts by weight of silica were dispersed in the resulting chitosan acid solution and stirred at 350 rpm for 1.2 hours at 55°C. Under stirring conditions, a 4% sodium hydroxide solution was slowly added to the resulting system to adjust the pH value of the system to 9.2, and then aged for 0.8 hours under the same conditions. The aged material is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. Then it is dried at 65°C until the moisture content of the material is 2.2%. Finally, it is pulverized to obtain the chitosan modified filler.

[0039] The preparation method of silica-coated nano-titanium dioxide is as follows: One part by mass of nano-titanium dioxide powder was dispersed in a mixed solvent consisting of 60 parts by mass of ethanol and 18 parts by mass of deionized water, and ultrasonically treated for 18 minutes to form a uniform suspension. Under room temperature and stirring conditions, 2 parts by mass of ammonia water with a mass concentration of 27% were added to the resulting suspension as a catalyst. Under stirring conditions, 0.2 parts by mass of tetraethyl orthosilicate were added dropwise to the system, with the dropping rate controlled to be completed in 1.8 hours, and the reaction continued for 2.5 hours after the addition was completed. After the reaction was completed, the product was centrifuged, the precipitate was washed twice with ethanol, and then dried at 75°C to obtain the silica-coated nano-titanium dioxide.

[0040] A method for preparing the above-mentioned acaricide composition includes the following steps: Weigh the obtained chitosan-modified filler, active ingredient, photosensitizer, pore-forming agent, dispersant, and wetting agent according to the specified ratio; Add the weighed components into the mixer for the first mixing, and mix for 14 minutes. The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be 11μm. The pulverized material is then mixed a second time for 28 minutes to obtain a wettable powder.

[0041] Example 5 An acaricide composition comprising, by weight, the following components: Ethoxyfenozide 22.5 parts and sodium alkyl ethyl sulfonate 22.5 parts; Polyvinyl alcohol (PVA-1092) 10 parts; 30 parts of chitosan-modified filler; 1.5 parts of silica-coated nano-titanium dioxide; PEG 6000, 6 parts; 7 parts potassium lignosulfonate; 2.5 parts of trisiloxane polyoxyethylene ether; The preparation method of chitosan-modified filler is as follows: Eight parts by weight of chitosan were dissolved in 450 parts by weight of acetic acid solution with a mass concentration of 1.5% to prepare chitosan acid solution; 100 parts by weight of bentonite were dispersed in the resulting chitosan acid solution and stirred at 450 rpm for 1.8 hours at 45°C. Under stirring conditions, a 2% sodium carbonate solution was slowly added to the resulting system to adjust the pH value of the system to 9.8, and then aged for 0.6 hours under the same conditions. The aged material is filtered, and the filter cake is washed with deionized water until the filtrate is neutral. Then it is dried at 75°C until the moisture content of the material is 2.0%. Finally, it is pulverized to obtain the chitosan modified filler.

[0042] The preparation method of silica-coated nano-titanium dioxide is as follows: One part by mass of nano-titanium dioxide powder was dispersed in a mixed solvent consisting of 90 parts by mass of ethanol and 12 parts by mass of deionized water, and ultrasonically treated for 12 minutes to form a uniform suspension. Under room temperature and stirring conditions, 4 parts by mass of ammonia water with a mass concentration of 25.5% were added to the resulting suspension as a catalyst. Under stirring conditions, 0.4 parts by mass of tetraethyl orthosilicate were added dropwise to the system, with the dropping rate controlled to be completed in 1.2 hours, and the reaction continued for 3.5 hours after the addition was completed. After the reaction was completed, the product was centrifuged, the precipitate was washed three times with ethanol, and then dried at 65°C to obtain the silica-coated nano-titanium dioxide.

[0043] A method for preparing the above-mentioned acaricide composition includes the following steps: Weigh the obtained chitosan-modified filler, active ingredient, photosensitizer, pore-forming agent, dispersant, and wetting agent according to the specified ratio; The weighed components are put into a mixer for the first mixing, and the mixing time is 11 minutes; The first mixed material is subjected to air jet milling, and the particle size D90 of the milled material is controlled to be 14μm. The pulverized material is then mixed a second time for 22 minutes to obtain a wettable powder.

[0044] Comparative Example 1 The only difference from Example 1 is that trisiloxane polyoxyethylene ether was not added.

[0045] Comparative Example 2 The only difference from Example 1 is that PEG 6000 was not added.

[0046] Comparative Example 3 The only difference from Example 1 is that nano-titanium dioxide that is not coated with nano-silica is directly selected.

[0047] Comparative Example 4 The only difference from Example 1 is that the filler base material that has not been modified with chitosan is directly selected.

[0048] Comparative Example 5 The only difference from Example 1 is that there is no film-forming agent.

[0049] Comparative Example 6 The only difference from Example 1 is that the components exceed the limits: 65 parts of active ingredient; 10 parts of film-forming polymer; 70 parts of chitosan-modified filler; 2 parts of photosensitizer; 5 parts of pore-forming agent; 6 parts of dispersant; and 3 parts of wetting agent.

[0050] Comparative Example 7 The only difference from Example 1 is that the components exceed the limits: 25 parts of active ingredient; 6 parts of film-forming polymer; 15 parts of chitosan-modified filler; 2 parts of photosensitizer; 5 parts of pore-forming agent; 6 parts of dispersant; and 3 parts of wetting agent.

[0051] Comparative Example 8 The only difference from Example 1 is that the amount of silica coating is too large, specifically: The preparation method of silica-coated nano-titanium dioxide is as follows: One part by mass of nano-titanium dioxide powder was dispersed in a mixed solvent consisting of 75 parts by mass of ethanol and 15 parts by mass of deionized water, and ultrasonically treated for 15 minutes to form a uniform suspension. Under room temperature and stirring conditions, 3 parts by mass of ammonia water with a mass concentration of 26.5% were added to the resulting suspension as a catalyst; Under stirring conditions, 0.8 parts by mass of tetraethyl orthosilicate were added dropwise to the system, with the dropping rate controlled to be completed in 1.5 hours, and the reaction continued for 3 hours after the addition was completed. After the reaction was completed, the product was centrifuged, the precipitate was washed three times with ethanol, and then dried at 70°C to obtain the silica-coated nano-titanium dioxide.

[0052] Comparative Example 9 The only difference from Example 1 is that no dispersant was added.

[0053] Performance testing: 1. Sample preparation: The acaricide compositions prepared in Examples 1-5 and Comparative Examples 1-9 and commercially available acaricides (the main active substance is etoxazole, 30% etoxazole suspension) were dispersed in 500 times the amount of deionized water to form a suspension. Vinegar was added to adjust the pH to 5.5 to obtain the sample.

[0054] 2. Wetting test: Fix fresh citrus leaves on the sample stage, use a pipette to take 5 μL of suspension and drop it onto the leaf surface. After standing for 3 seconds, take an image with a contact angle measuring instrument and calculate the contact angle. Test 5 different sites for each sample and take the average value. The target contact angle is ≤60°. At the same time, refer to the "Determination of Wetting Properties of Pesticide Wettable Powders (GB / T 5451-2001)" to evaluate the wetting speed of the powder in water.

[0055] 3. Refer to GB / T 16150-1995 "Determination of Fineness of Pesticide Powders and Wettable Powders" and GB / T 14825-1993 "Determination of Suspension Rate of Pesticide Wettable Powders" for testing.

[0056] The test results are shown in Table 1; Table 1 Performance test results of the examples and comparative examples

[0057] The acaricide composition prepared in the examples effectively solves the core pain points of traditional acaricides by means of the precise ratio and synergistic effect of each functional component. Trisiloxane polyoxyethylene ether can efficiently improve the wettability of the liquid on hydrophobic leaf surfaces, polycarboxylate or lignin sulfonate dispersant ensures rapid wetting and uniform dispersion of powder, chitosan modified filler and film-forming polymer synergistically control powder fineness and improve suspension stability, and pore-forming agent and silica-coated nano titanium dioxide further optimize the overall performance of the system.In the comparative examples, Comparative Example 1, lacking the addition of trisiloxane polyoxyethylene ether, lost the superspreading function of the wetting agent, making it difficult for the drug solution to spread on the hydrophobic leaf surface, resulting in a significant increase in contact angle and a significant extension of wetting time. Comparative Example 2, lacking the addition of polyethylene glycol porogen, although the porogen does not directly affect the initial wettability and fineness, disrupts the microscopic stability of the suspension system, leading to a significant decrease in suspension rate. Comparative Example 3 used uncoated nano-titanium dioxide; the exposed nano-titanium dioxide only underwent slight agglomeration during dispersion, having little impact on the wettability of the drug solution and the fineness of the powder. Therefore, the contact angle, wetting time, and fineness data were close to those of the examples, with only the suspension rate differing. Slightly reduced; Comparative Example 4 used an unmodified chitosan filler matrix, which lacked the hydrophilic-hydrophobic synergistic segments of chitosan on its surface, making it unable to form a tight network structure with the film-forming polymer. This weakened the spreading ability of the drug solution on the leaf surface and disrupted the uniformity of powder dispersion, resulting in increased contact angle, prolonged wetting time, excessive fineness, and a sharp drop in suspension rate; Comparative Example 5 did not add a film-forming polymer, and the film-forming polymer mainly plays a role in the subsequent adhesion and formation of the drug film, having no direct impact on initial wettability, powder fineness, and suspension rate. Therefore, its initial test indicators were very similar to those of the examples; Comparative Example 6 had excessive amounts of active ingredients and chitosan-modified filler, and excessive active ingredients easily... Excessive filler can cause particle agglomeration, disrupting the component ratio balance and preventing wetting agents and dispersants from fully functioning. This results in increased contact angle, prolonged wetting time, excessive fineness, and a significant decrease in suspension rate. In Comparative Example 7, although the amounts of active ingredient, film-forming polymer, and chitosan-modified filler were insufficient, the crucial wetting agent and dispersant were not lacking, allowing for partial wetting of the drug solution and dispersion of the powder. Therefore, the contact angle, wetting time, and fineness only slightly deviated from the example, with the decrease in suspension rate due to insufficient film-forming support and dispersion power; overall, the performance was acceptable. In Comparative Example 8, the coating amount of silica-coated nano-titanium dioxide was too large. Although the excessively thick silica layer did not damage the nano-titanium dioxide... Titanium's basic dispersibility has little impact on wettability and fineness, but it slightly hinders its synergistic effect with other components, resulting in a slight decrease in suspension rate. Comparative Example 9, without the addition of a dispersant, loses the dispersant's function of preventing particle agglomeration through steric hindrance and electrostatic repulsion. The powder is difficult to disperse uniformly in water, resulting in severe particle agglomeration, which leads to an increased contact angle, a significantly prolonged wetting time, excessive fineness, and a significant decrease in suspension rate. The commercially available 30% etoxazole suspension, lacking a synergistic system of chitosan-modified filler and trisiloxane polyoxyethylene ether, lacks efficient wetting and film-forming support. Its wettability, fineness, and suspension rate are all inferior to those of the examples, demonstrating the technical limitations of traditional formulations.

[0058] Examples 1-5, and Comparative Examples 3, 5, and 7-8 from Table 1, which showed good basic performance, were selected and tested with commercially available samples: Insect sample preparation: Sensitive strains of citrus red spider mites were cultured indoors (adults and nymphs were the main targets for testing; eggs and larvae were not evaluated as they were difficult to distinguish with the naked eye). They were raised on citrus leaves under environmental conditions of 25℃, 60% relative humidity, and a photoperiod of 16L:8D. One-year-old citrus seedlings with uniform growth (one seedling per pot, with ≥30 leaves) were selected. The waxy coating on the leaves was washed off with deionized water 24 hours in advance. The prepared instruments included HPLC (for measuring etoxazole content), a handheld sprayer (0.2MPa), a simulated rainfall device, a constant temperature incubator, and a temperature and humidity recorder.

[0059] Leaf rain and persistence effect test: Foliar rain effect test: All samples were sprayed evenly at a rate of 60 L / acre (3 replicates, blank control sprayed with an equal volume of pH 5.5 hard water). After spraying, the samples were placed in an environment of 25℃ and 60% relative humidity to air dry for 2 hours to ensure film formation. In the rain effect test, a simulated rainfall device was used to set up moderate intensity rainfall (20 mm / h) for 30 minutes (total rainfall 10 mm), with raindrop diameter of 1.5-2 mm and rainfall height of 1.5 m. After the rainfall, the plants were air-dried, and leaves were collected at 0 h and 24 h. The etoxazole residue rate was determined by HPLC (content after flushing / content before flushing × 100%). At 24 h, each leaf was inoculated with 50 citrus red spider mite nymphs (3rd-4th instar visible to the naked eye) and 50 adult mites (ratio 1:1). After 48 h, the activity status of the mites (crawling or still) was observed by the naked eye, and the mortality rate (still and unresponsive to touch was considered dead) was calculated to determine the control effect.

[0060] Durability test: After application, the plants were placed in a rain-protected natural environment (average daily temperature 20-30℃, relative humidity 55-70%) and continuously monitored for 1d, 7d, 14d, 21d, and 28d. At each time point, 50 nymphs and 50 adults were randomly selected from the leaves and inoculated. The control effect was visually assessed after 48h. At the same time, the residual amount was determined by HPLC at 1d, 14d, and 28d, and decay curves were plotted.

[0061] When determining the effectiveness, excellent rain spray effect requires a residual rate of ≥80% and a control effect of ≥75%, while excellent long-lasting effect requires a control effect of ≥80% for a duration of ≥21 days.

[0062] Acaricide efficacy test: Fresh citrus leaves (5cm in diameter) were taken, and the petioles were wrapped with damp cotton to maintain moisture. The leaves were placed in petri dishes, and all samples were sprayed with a 500-fold dilution and then air-dried for 2 hours. Each leaf was inoculated with 25 3-4 instar nymphs and 25 adult mites. After 48 hours, the activity status was observed visually, and the corrected mortality rate was calculated as ((control mortality rate - treatment mortality rate) / (1 - control mortality rate) × 100%). Simultaneously, oviposition traces (visible clusters of tiny eggs) of surviving adult mites within 7 days were recorded to roughly assess the oviposition inhibition effect. The judgment criteria were a corrected mortality rate ≥85% for nymphs and ≥70% for adults.

[0063] Storage effect test: The samples were placed in sealed aluminum foil bags (20g / bag, 3 replicates) and placed in an oven at 54℃ for 14 days (accelerated heat storage), a refrigerator at 0℃ for 7 days (cold storage), and an environment at 25℃ and 60% relative humidity for 6 months (room temperature storage). Post-storage test: The appearance was observed for clumping or layering. The decomposition rate of the active ingredient was measured by HPLC. After dilution, the corrected mortality rates of nymphs and adults were measured according to the above-mentioned acaricidal effect test method, and the activity retention rate was calculated as (mortality rate after storage / mortality rate before storage × 100%). Stable storage requires no abnormal appearance after heat storage, a decomposition rate ≤5%, and an activity retention rate ≥90%.

[0064] The experimental results are shown in Table 2; Table 2 compares the mite-killing effects of the examples, some comparative examples, and commercially available products.

[0065] The acaricide composition prepared in the examples exhibits significant data advantages and consistent performance: its foliar rain residue rate and control efficacy remain consistently high; the sustained control effect decreases gradually from 14 to 21 days; its killing effect on nymphs and adults and its oviposition inhibition are stable and prominent; after accelerated heat storage, there are no abnormal appearances, minimal decomposition of active ingredients, and sufficient retention of activity. These advantages stem from the synergistic effect of each functional component. Trisiloxane polyoxyethylene ether ensures efficient spread of the pesticide solution on hydrophobic leaf surfaces; polycarboxylate or lignin sulfonate ensures uniform dispersion of the powder; chitosan-modified filler and film-forming polymer synergistically form a tightly adhered mesh film on the leaf surface, firmly fixing the etoxazole particles to resist rain erosion; polyethylene glycol porogen constructs breathable micropores within the film to prevent film failure; silica-coated nano-titanium dioxide ensures storage stability while enabling late-stage degradation of the film; and the combination of etoxazole and alkyl ethyl sulfonate covers the control needs of different mite life stages. In the comparative examples, Comparative Example 3, using uncoated nano-titanium dioxide, was prone to uneven degradation of the pesticide film when exposed to the natural environment for extended periods, resulting in a sharp drop in the 21-day long-lasting control effect. Slight clumping also occurred after heat storage, demonstrating the protective effect of the silica coating layer on the stability of the pesticide film. Comparative Example 5, without the addition of a film-forming polymer, while initially showing no impact on acaricidal activity and storage stability, lacked a film-forming agent. The chitosan-modified filler could not form a complete mesh support structure, significantly reducing the adhesion between the pesticide film and the leaf surface, making it easily washed away by rain. Therefore, the leaf residue rate and control effect were significantly lower than in the examples. Comparative Example 7, due to insufficient amounts of active ingredient, film-forming polymer, and chitosan-modified filler, showed a weakened killing effect on adult mites and an inhibited oviposition effect due to insufficient active ingredient. Insufficient film-forming agent and modified filler prevented the formation of a stable film. The film structure of the control sample resulted in lower foliar rain residue and longer-lasting control effects compared to the example, highlighting the importance of balanced component dosage for overall performance. In Comparative Example 8, the silica coating on nano-titanium dioxide was too thick. While the excessively thick silica layer did not destroy the basic function of the nano-titanium dioxide, it slightly hindered its synergistic effect with other components and affected powder dispersibility. This led to slightly lower foliar rain control effects and activity retention after heat storage compared to the example, confirming the necessity of precise control of coating amount. The commercially available 30% etoxazole suspension, lacking a synergistic film-forming system of chitosan-modified filler and film-forming polymer, lacked efficient wetting, spreading, and adhesion support, and did not coat the photosensitizer. Therefore, its foliar rain residue, long-lasting control, and storage stability were far inferior to the example, highlighting the breakthrough of this invention in addressing the shortcomings of traditional formulation technology. The natural mortality rate and zero oviposition inhibition rate of the blank group provided a benchmark for evaluating the effects of all samples, ensuring the authenticity of the performance differences between the example and the comparative example and eliminating the interference of environmental factors.

[0066] In Example 1, the antibacterial activity was verified using the plate count method, with sterile water at pH 5.5 as a blank control. *Anthracnose citrus*, *Early blight causal agent of tomato*, and *Downy mildew causal agent of cucumber* (all activated on PDA medium at 25°C for 7 days) were selected as target pathogens. Pathogen colonies were scraped and added to sterile physiological saline, shaken for 10 minutes, filtered through gauze, and the spore suspension concentration was adjusted to 1×10⁻⁶ using a hemocytometer. 6 1 mL of spore suspension was taken and mixed with 1 mL of 500-fold diluted wettable powder from Example 1 (pH 5.5) and 1 mL of sterile water for blank control. The mixtures were co-cultured at 25°C in the dark for 24 h (3 replicates per group). The mixtures were then serially diluted with sterile physiological saline to 10⁻⁶. 3 10 4 10 5 Each dilution was prepared by spreading 100 μL of each solution onto a PDA plate (3 replicates per dilution). After drying, the plates were inverted and incubated at 25°C for 7 days. The average colony count was calculated for plates with colony counts between 30 and 300. The inhibition rate was calculated using the formula (average colony count of the blank group - average colony count of Example 1 group) / average colony count of the blank group × 100%. The results showed that Example 1 had an inhibition rate of 72±3% against citrus anthracnose, 68±3% against tomato early blight, and 65±3% against cucumber downy mildew, all reaching a medium-to-high level of antibacterial activity, confirming its synergistic effect of "killing mites and fighting bacteria". The inhibition rate of the blank group against the three pathogens was 0±1%, eliminating the interference of solvent and environmental factors.

Claims

1. A mite-killing composition, characterized in that, Based on parts by mass, it includes the following components: 30-60 parts of active ingredient; 8-15 parts of film-forming polymer; 20-60 parts of chitosan-modified filler; 1-3 parts photosensitizer; 3-7 parts of pore-forming agent; 4-8 parts dispersant; 2-4 parts wetting agent; The active ingredient is a combination of etoxazole and alkyl ethyl sulfonate; The photosensitizer is silicon dioxide-coated nano-titanium dioxide; The acaricide composition is a wettable powder; The preparation method of the chitosan-modified filler is as follows: S1a. Dissolve 5-20 parts by weight of chitosan in 200-500 parts by weight of acetic acid solution with a mass concentration of 1-3% to prepare chitosan acid solution; S1b. Disperse 100 parts by weight of the filler matrix in the chitosan acid solution obtained in step S1a, and stir at 300-500 rpm for 1-2 hours at 40-60℃. S1c. Under stirring conditions, slowly add an alkaline precipitant to the system obtained in step S1b to adjust the pH of the system to 9.0-10.0, and then age it for 0.5-1 hour under the same conditions; S1d. The material after aging in step S1c is filtered, the filter cake is washed with deionized water until the filtrate is neutral, then dried at 60-80℃ until the moisture content of the material is less than 3.0%, and finally pulverized to obtain the chitosan modified filler. The method for preparing the silica-coated nano-titanium dioxide is as follows: S2a. Disperse 1 part by weight of nano-titanium dioxide powder in a mixed solvent consisting of 50-100 parts by weight of ethanol and 10-20 parts by weight of deionized water, and sonicate for 10-20 minutes to form a uniform suspension. S2b. Under room temperature and stirring conditions, add 1-5 parts by mass of ammonia water with a mass concentration of 25-28% as a catalyst to the suspension obtained in step S2a; S2c. Under stirring conditions, add 0.1-0.5 parts by mass of tetraethyl orthosilicate dropwise to the system of step S2b, control the dropping rate to complete the dropping in 1-2 hours, and continue the reaction for 2-4 hours after the dropping is completed; S2d. After the reaction is complete, the product is centrifuged, the precipitate is washed with ethanol 2-3 times, and then dried at 60-80℃ to obtain the silica-coated nano titanium dioxide. The mass ratio of etoxazole to alkyl ethyl sulfonate is 1:0.5-1:2; the wetting agent is trisiloxane polyoxyethylene ether; the pore-forming agent is polyethylene glycol; the dispersant is polycarboxylate or lignin sulfonate; and the film-forming polymer is one or more of chitosan or polyvinyl alcohol.

2. The acaricide composition according to claim 1, characterized in that, The filler matrix is ​​selected from at least one of kaolin, diatomaceous earth, attapulgite, light calcium carbonate, fumed silica, or bentonite.

3. The acaricide composition according to claim 1, characterized in that, The alkaline precipitant mentioned in step S1c is an aqueous solution of sodium hydroxide or sodium carbonate.

4. The application of the acaricidal composition as described in any one of claims 1-3 in the control of plant mites, characterized in that, The acaricide composition is dispersed in 300-800 times its volume of water to form a suspension, and then sprayed onto the plant surface.

5. The application of the acaricidal composition as described in claim 4 in the control of plant mites, characterized in that, Before spraying, add an acidity regulator to the suspension to adjust its pH value to 5.0-6.0; the application rate during spraying is 30-60L per acre.

6. The application of the acaricidal composition as described in claim 4 in the control of plant mites, characterized in that, The plant pest is at least one of the following: spider mite, red spider mite, citrus red spider mite, gall mite, tarsier mite, or leafminer mite; the plant is at least one of the following: citrus, vegetables, fruit trees, or tea trees.

Citation Information

Patent Citations

  • Miticidal composition

    CN104996438A

  • A mite-killing composition

    CN118661737B

  • Preparation method of magnetic rectorite / chitosan nano-grade composite material

    CN102516607A

  • Insecticidal composition

    CN107318861A

  • Acaricide preparation and application thereof

    CN108684681A